Study of growth differentiation factor 9 (GDF9) gene polymorphism in Indonesian goats - Elieser, Simon; Maharani, Dyah; Budisatria, I Gede Suparta; Batubara, Aron; Hariyono, Dwi Nur Happy; Sari, Aprilianna Putri Zahara Nafsina Luvita (2018)
A member of growth factor and a member of the transforming growth factor β superfamily, growth differentiation factor 9 (GDF9) has a critical role in prolificacy of sheep and goat. The aim of this study was to analyze the exon 1 of GDF9 gene in Indonesian goats. For this purpose, 78 blood samples representing ten Indonesian goat breeds: Gembrong (GB), Senduro (SD), Peranakan Etawah (PE), Boerawa (BR), Boerka (BK), Kosta (KT), Muara (MR), Boer (BO), Samosir (SM) and Kacang (KC) were collected. An exonic region of GDF9 gene, 462 bp was amplified using specific primers. Two SNPs were identified based on reference and direct sequencing, SNP 306G>A and SNP 239C>A, respectively. SNP 306G>A was used to genotype all animals using RFLP method with HhaI restriction enzyme. The results revealed an absence of polymorphism of GDF9 gene at SNP 306G>A in all animals investigated. Hence, a further attempt should be addressed to investigate this SNP 239C>A of GDF9 gene which may influence the prolificacy of goats.